Students’ Perspectives on Concepts, Factors, and Models Related to the Attainment of Achievement - Titik Kristiyani; Faturochman Faturochman (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2018)
This study aimed to explore concepts, factors affecting, and achievement models, from the perspective of tertiary students in Yogyakarta. Respondents (N = 533) were students of a private university in Yogyakarta. Data was collected through an open-ended questionnaire for all respondents, and in-depth interviews with 23 of these. Data were analyzed using content analysis techniques for responses to the answers provided. The results show that the concept of achievement, according to the perspective of the students, is differentiated between into definitions of achievement, and the criteria of what may to be considered to be achievements. The definition of achievement, according to the students, is something which is unique to this finding, with the emergence of non-academic achievement and excellence in competition with others. The criteria discovered, for a person to be considered to be an achiever, include compliance with goals (both personal and social) and the presence of the element of development. The presence of the suitability of social goals, is another unique thing found in this study. Factors which influence achievement include ‘input’ (personal capacities), and ‘process’ (the learning process)’. The external conditions which emerged in this finding took the form of other unique matters, found in the local culture. The dynamics of reaching achievement begin with ‘input’ (cognitive capacity, personal skills, motivation), and external conditions (which give rise to academic learning behaviors with the support of self-efficacy), for future learning achievements which are more optimal, with the attainment of personal and social goals.